PENGARUH PUPUK CAIR MULTI FUNGSI TERHADAP KESUBURAN TANAH PADA TANAMAN SIRSAK (Annona muricata L.) HASIL SAMBUNG PUCUK - Agnes Debora Buulolo; M. Wasito; Ruth Riah Ate Tarigan (Fakultas Pertanian, Universitas Janabadra, 2023)
Soursop plants is a plant that grows wild, then developed into a yard plant. Soursop plants (Annona muricata L.) grow in tropical climates and can adapt well to lowlands up to 800 m above sea level. This study aims to determine the effect of multi-functional liquid fertilizer on soil fertility in soursop plants (Annona muricata L.) from shoot joints. This research was conducted on Jl Madura, Kelurahan Pahlawan, North Binjai District, Binjai City, Noorth Sumatra Province, from January 2023 to March 2023. This study used the Non-Factorial Group Randomized Design (GRD) experimental method with 4 leves of treatment (without liquid fertilizer treatment, 2 ml/ liter of water, 4 ml/ liter of water, and 6 ml/ liter of water) so that there were 16 experimental units. Each experimental unit consists of 3 sample plants, so that the total plant size is 48 experimental units. Observation variables in this study include plant height, number of leaves, leaf area, number of branches, trunk diameter, and branch length. The result showed that the effect of applying multi-functional liquid fertilizer at a dose of 6 ml/ liter of water had a significantly different influence on the age of soursop plants three months after transplanting on plant height, number of leaves, leaf area, number of branches, trunk diameter, and branch length. This is significantly different from the dose of liquid fertilizer 0, 2 ,and 4 ml/ liter of water.